Phosphatidylinositol 3-kinase delta pathway: a novel therapeutic target for Sjögren's syndrome. Issue 2 (24th November 2018) - Nayar, Saba; Campos, Joana; Smith, Charlotte G; Iannizzotto, Valentina; Gardner, David H; Colafrancesco, Serena; Pipi, Elena; Kollert, Florian; Hunter, Kelly J; Brewer, Charlotte; Buckley, Christopher Dominic; Bowman, Simon J; et al.
Abstract : Background: The phosphatidylinositol 3-kinase delta isoform (PI3Kδ) belongs to an intracellular lipid kinase family that regulate lymphocyte metabolism, survival, proliferation, apoptosis and migration and has been successfully targeted in B-cell malignancies. Primary Sjögren's syndrome (pSS) is a chronic immune-mediated inflammatory disease characterised by exocrine gland lymphocytic infiltration and B-cell hyperactivation which results in systemic manifestations, autoantibody production and loss of glandular function. Given the central role of B cells in pSS pathogenesis, we investigated PI3Kδ pathway activation in pSS and the functional consequences of blocking PI3Kδ in a murine model of focal sialoadenitis that mimics some features of pSS. Methods and results: Target validation assays showed significant expression of phosphorylated ribosomal protein S6 (pS6), a downstream mediator of the phosphatidylinositol 3-kinase delta (PI3Kδ) pathway, within pSS salivary glands. pS6 distribution was found to co-localise with T/B cell markers within pSS aggregates and the CD138+ plasma cells infiltrating the glands. In vivo blockade of PI3Kδ activity with seletalisib, a PI3Kδ-selective inhibitor, in a murine model of focal sialoadenitis decreased accumulation of lymphocytes and plasma cells within the glands of treated mice in the prophylactic and therapeutic regimes. Additionally, production of lymphoid chemokines and cytokines associated with ectopic lymphoneogenesis and, remarkably, saliva flow and autoantibody production, were significantly affected by treatment with seletalisib. Conclusion: These data demonstrate activation of PI3Kδ pathway within the glands of patients with pSS and its contribution to disease pathogenesis in a model of disease, supporting the exploration of the therapeutic potential of PI3Kδ pathway inhibition in this condition.